2010
DOI: 10.1021/cg1003098
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Investigations of Methane−Hydrate Films Formed on a Glass Surface

Abstract: Methane clathrate formation on water films without previous hydrate formation history was studied. It was found that hydrates form in two layers, each with a clearly distinct morphology. As the clathrate aged, this difference in morphology tended to disappear. Higher driving forces produced smaller hydrate grains and smoother surfaces than lower driving forces within the water film. The converse was true for hydrate formed on the periphery. A third hydrate layer growing outside of the original water boundary w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 35 publications
6
71
0
Order By: Relevance
“…Individual grain size decreases with increasing subcooling, and therefore grain density is lower towards higher temperatures. The latter agrees with previous work done for pure methane hydrate . Both systems B and C exhibited a change in crystal habit toward lower subcoolings (Figure ).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Individual grain size decreases with increasing subcooling, and therefore grain density is lower towards higher temperatures. The latter agrees with previous work done for pure methane hydrate . Both systems B and C exhibited a change in crystal habit toward lower subcoolings (Figure ).…”
Section: Resultssupporting
confidence: 56%
“…The latter agrees with previous work done for pure methane hydrate. [14,24,25] Both systems B and C exhibited a change in crystal habit toward lower subcoolings ( Figure 5). For the system containing Inhibitor B, this transition was evident at ΔT sub = 2.2 K, whereas for system C the transition was observed at ΔT sub = 1.4 K. This dependence of the crystal habit on subcooling, namely the density of grains, ridges, and dendrites, has been reported for several KHIs and THIs, although the particular morphologies are different in each case.…”
Section: Exptmentioning
confidence: 99%
“…Otherwise, a system may be in a metastable state from seconds to hours/days because nucleation of the hydrates is a stochastic process. Because the effect of the "memory" on the crystal growth behavior was concerned as observed on the crystal morphology of the hydrate formed on the liquid water wetting the glass surface, [21] we performed some experiments without the memory effect and confirmed that the results were identical with those with the memory effect.…”
Section: Methodsmentioning
confidence: 56%
“…The presence of MEG had a dramatic effect on halo propagation. Previous studies [31,32] had reported smooth halos, but never the three-dimensional faceted habit observed in Figure 4. The results observed in Figure 4 were highly reproducible as shown in Figure 5.…”
Section: Water + Ch 4 + Meg (W Meg = 10%)mentioning
confidence: 65%